A Study of Regional Rural Banks : The Conundrum of Managing Inclusion with Sustainability - Yadav, Amar Nath; Singh, Sukhbir; Jaiswal, Ashish (Indian Journal of Finance, 2023)
Regional rural banks (RRBs) were created with the vision to expand banking services to the underprivileged population in rural areas sustainably and effectively. However, after a decade of inception, such institutions’ financial viability and survival became questionable, which posed a serious concern for policymakers. As a result, the Government of India and its regulators initiated various policies in the late 1990s to make these institutions financially viable and self-sustainable in the long run. These policy interventions have successfully transformed the financial health of RRBs to some extent. However, in this process, it was widely discussed that the RRBs were moving away from their original mandate. However, no detailed study has been published so far to investigate this dimension. This paper tried to bridge this gap by exploring the performance of RRBs with respect to the objectives for which they were incorporated through evidence based on data. This is the first study that provides a comparison of the performance of RRBs with other banks at the service area level. The study observed that RRBs have remained true to their original mandate and are still doing relatively better in comparison to other commercial banks in their area of operation.